Implementation of different strategies of the “ActTeens” intervention for adolescents: a process evaluation - Gessika Castilho dos Santos; Jadson Marcio da Silva; Renan Camargo Correa; Rodrigo de Oliveira Barbosa; Gabriel Pinzon; Maria Carolina Juvêncio Francisquini; Thais Maria de Souza Silva; Antonio Stabelini Neto (Revista Brasileira de Atividade Física e Saúde)
Multicomponent programs to promote physical activity have shown promise to help adolescents to increase physical activity levels. Although evaluation of the intervention implementation process is important, information about this evaluation is rarely reported. This observational study aimed to evaluate the implementation of a 12-week physical activity intervention program for adolescents. The ActTeens program consists of three components: (1) structured physical activity sessions; (2) self-monitoring associated with daily goal setting; (3) healthy lifestyle messages (mHealth). The evaluation of the process was carried out through observations and self-reported information from the students. Fifty-one adolescents (37.5% girls) answered the questionnaire. Overall, the reach was 73.3%, retention rate 96.3%, and satisfaction with the intervention was high (score 5). The structured sessions presented high fidelity, and good acceptability among adolescents, with an average attendance rate of 93.7%. Participants rated the sessions as enjoyable and the teacher’s role as excellent. Adherence to self-monitoring (goal setting with a pedometer) was moderate and 57.8% of adolescents reported using the device daily. In addition, adolescents reported that the use of a pedometer increased their motivation to practice physical activity (72.4%). Satisfaction with the messages was considered low, with only 37.8% agreeing that the messages promoted the adoption of a healthy lifestyle. In conclusion, the structured sessions and the self-monitoring showed good acceptability among adolescents, and these strategies were considered relevant to promote a more physically active lifestyle. However, the component mHealth, when used as a single strategy, did not aid the adoption of healthy behavior.